Population Pharmacokinetics of Levobupivacaine During Transversus Abdominis Plane Block in Children. Issue 3 (June 2020) - Vincent, Marc; Mathieu, Olivier; Nolain, Patrick; Menacé, Cecilia; Khier, Sonia
Abstract : Background: Levobupivacaine is commonly used during transversus abdominis plane (TAP) block in pediatric patients. However, the dosing regimen is still empirical, and the pharmacokinetic properties of levobupivacaine are not considered. Here, the pharmacokinetics of levobupivacaine during an ultrasound-guided TAP block were evaluated to optimize dosing regimen, regarding the between-subject variability (BSV) and the volume of levobupivacaine injected. Method: The clinical trial (prospective, randomized, double-blind study protocol) was conducted in 40 children aged 1–5 years, who were scheduled for inguinal surgery. Each patient received 0.4 mg/kg of levobupivacaine with a volume of local anesthesia solution adjusted to 0.2 mL/kg of 0.2% or 0.4 mL/kg of 0.1% levobupivacaine. Blood samples were collected at 5, 15, 20, 25, 30, 45, 60, and 75 minutes after the block injection. The population pharmacokinetic analysis was performed using the NONMEM software. Results: From the pharmacokinetic parameters obtained, median Cmax, tmax, , and area under the concentration versus time curve were 0.315 mg/L, 17 minutes, and 41 mg/L·min −1, respectively. BSV of clearance was explained by weight. At the dose regimen of 0.4 mg/kg, none of the infants showed signs of toxicity, but in 13 patients, TAP block failed. After analysis, BSV for absorption rate constant, distribution volume, and clearance were 81%, 47%, and 41%, respectively. Residual unexplained variability was estimated to be 14%. Conclusions: For improved efficiency in the pediatric population, the dose of levobupivacaine should be greater than 0.4 mg/kg. Children's weight should be considered to anticipate any risk of toxicity. Abstract : Supplemental Digital Content is Available in the Text.